Viticultural and Pre-Fermentation Strategies to Reduce Alcohol Levels in Wines - Francesca Coppola; Bruno Testa; Mariantonietta Succi; Gianluca Paventi; Catello Di Martino; Massimo Iorizzo (Foods)
Changes in lifestyles, as well as the growing attention to healthy nutrition, led to the increasing demand for wines with reduced alcohol content. The reduction in fermentable sugars in the pre-fermentation stage of wine is one of the common methods for the production of wines with lower alcohol content. Viticultural practices such as early harvesting, use of growth regulators, reducing leaf area to limit photosynthetic rate, and pre-harvest irrigation are utilized. Additionally, techniques such as juice dilution, juice filtration with membranes, and the use of enzymes (e.g., glucose oxidase) are also employed in the pre-fermentation stage. This review summarizes and describes the classic and innovative viticultural and pre-fermentation techniques used to reduce the alcohol content and their main impact on the compositional characteristics of wine.